Measurement of swimming anaerobic capacity
Blood lactate measures were shown not to be related to anaerobic capacity. Swimmers of different abilities served as subjects. They were measured for true anaerobic capacity. For performance on a 45 sec swim bench test the relationship was r = .82, and on a 30 sec arm cranking Wingate test it was r = .86 with anaerobic capacity. Either of these two tests can be used to provide an estimate of anaerobic capacity. Implications. In the past there has been a preoccupation with strength measures as being the best indicators of sprinting ability. The tests used in this study offer a reasonable alternative. It might even be more valuable to use both the swim bench and Wingate tests together to estimate anaerobic capacity rather than either singly. Recently, there have been studies emerging which relate anaerobic peak or mean power to sprinting performance. In some there have been impressive correlations reported while in others the values have not been nearly as substantial. The common error in those which report low values is that the ability range of subjects is quite restricted. For accurate correlational studies, the range of apacities measured needs to be extensive. In this particular ICAR study, the ability range of the subjects was sufficiently varied to yield accurate statistics. For anaerobic capacity measurement and possible talent identification, either of these tests would serve a good practical purpose. It is always desirable to use a very specific and accurate test, but in swimming centers that do not have sophisticated scientific support, these tests will differentiate between swimmers of differing capacities with an acceptable degree of accuracy. (ICAR 1990-91 Report)